The struggle over borders : cosmopolitanism and communitarianism - De Wilde, P. (Pieter), 1980- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2019)
"As we will demonstrate in this book, the new fault lines around globalization can no longer be fully captured along the classic redistributional left-right axis. In important respects, they run perpendicular to it. Since the end of the Cold War, parties of the mainstream Left and Right, which had transformed themselves in the decades before from 'class' to catch-all parties (Kirchheimer 1965), have converged further on pro-globalization positions on a range of issues, such as support for European integration, the North American Free Trade Agreement (NAFTA) and trade agreements such as TTIP. Even on immigration, probably the most divisive of the issues related to globalization, differences between the mainstream Left and Right have become much smaller than they used to be - both because mainstream left parties have distanced themselves from earlier experiments with multicultural policies and because Conservatives have, at least in large parts of Western Europe, embraced pro-immigration views"--
Machine generated contents note: 1. Cosmopolitanism and Communitarianism - How Globalization is Reshaping Politics in the Twenty-First Century Ruud Koopmans and Michael Zurn; I. Domestic Impacts: 2. Why are Elites More Cosmopolitan than Masses? Oliver Strijbis, Celine Teney and Marc Helbling; 3. Mass Opinions: Globalization and Issues as Axes of Contention Bernhard Wessels and Oliver Strijbis; 4. Mapping Policy and Polity Contestation about Globalization: Issue Linkage in the News Pieter De Wilde; II. Supranational and Cross-level Analyses: 5. Who is the Most Frequent Traveller? The Cosmopolitanism of National, European, and Global Elites Oliver Strijbis; 6. Globalization Conflict in International Assemblies: Cleavage Formation beyond the State? Pieter De Wilde, Wiebke Junk and Tabea Palmtag; 7. Who are the Cosmopolitans and the Communitarians? Claims-Making across Issues, Polity Levels and Countries Ruud Koopmans; III. Conclusion: Conclusion. The Defects of Cosmopolitan and Communitarian Democracy Wolfgang Merkel and Michael Zurn.
Includes bibliographical references and index.
Keywords: Globalization -- Political aspects; Cosmopolitanism; Communitarianism; Right and left (Political science)